P PENGEMBANGAN MEDIA BUKU CEPAT UNTUK PENGENALAN LAMBANG 1-5 BILANGAN PADA PESERTA DIDIK HAMBATAN INTELEKTUAL - Kristina Nopalita Nainggolan; Irah Kasirah; Wuryani Wuryani (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This media development aims to produce a learning media that help students with intellectual disabilities in recognizing numbers easily and pleasantly. The research was conducted by using the Research and Development (R & D) method. Data collection was carried out using the ADDIE model without any implementation due to the corona virus pandemic situation. The evaluation technique is carried out by validation process by the media experts, material experts and intellectual disabilities experts to assess the quality of the media. The evaluation results show that the quick book media can be used to recognition number 1-5 to students with intellectual disabilities